Perancangan Sistem Inventory Menggunakan ODOO pada PT. Sectbillindo Raya Utama - Alvin Marganti Manaek Putra; Lufty Abdilah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The research conducted by the author aims to implement an inventory recording system at PT. Sectbilindo Raya Utama. The research was conducted in order to facilitate PT. Sectbillindo Raya Utama in carrying out work, to minimize errors in data collection. The method used in the research is RAD which can support the ERP system, the RAD method is used because it is suitable for research. This research was conducted with the needs planning stage, at this stage the authors conducted a needs analysis needed to support the inventory process at PT. Sectbillindo Raya Utama, at the design workshop stage the author uses the Unifield Modeling Language (UML) modeling design, and at the implementation stage the author applies an existing system at PT. Sectbillindo Raya Utama, as well as looking for testing after carrying out the implementation stage. The results of this study were carried out by implementing an ERP system using the Odoo14 application with the Inventory module to record stock of goods.